Structural properties of enterprise quality management system - Трищ, Роман Михайлович; Горбенко, Наталья Андреевна (Technology audit and production reserves, 2014)
It is suggested to consider the quality management system (QMS) as a large complex system and applying appropriate analysis methods, especially at the designing stage, since it gives grounds to the system model and mistakes, made at this stage, are the most costly and hard to amend. For analyzing the system, it is suggested using the theory of relations with carrying out the structural analysis that allows providing information about the "loading" rate and importance of system elements, comparing the systems with other structures, obtaining data on "weaknesses" of the system, that will enable timely improving and correcting the system. It is suggested to assess the quality management system according to such system properties as system coherence, process rank, system persistence that will give a quantitative characterization of the system at the designing stage. The proposed toolkit can be used in making decisions on developing a quality management system at its early designing stage, in order to avoid errors and ensure the efficiency of the system under development.